Graph Convolutional Networks for multi-modal robotic martial arts leg pose recognition - Yao, Shun; Ping, Yihan; Yue, Xiaoyu; Chen, He (Frontiers in Neurorobotics, 2025)
IntroductionAccurate recognition of martial arts leg poses is essential for applications in sports analytics, rehabilitation, and human-computer interaction. Traditional pose recognition models, relying on sequential or convolutional approaches, often struggle to capture the complex spatial-temporal dependencies inherent in martial arts movements. These methods lack the ability to effectively model the nuanced dynamics of joint interactions and temporal progression, leading to limited generalization in recognizing complex actions.MethodsTo address these challenges, we propose PoseGCN, a Graph Convolutional Network (GCN)-based model that integrates spatial, temporal, and contextual features through a novel framework. PoseGCN leverages spatial-temporal graph encoding to capture joint motion dynamics, an action-specific attention mechanism to assign importance to relevant joints depending on the action context, and a self-supervised pretext task to enhance temporal robustness and continuity. Experimental results on four benchmark datasets—Kinetics-700, Human3.6M, NTU RGB+D, and UTD-MHAD—demonstrate that PoseGCN outperforms existing models, achieving state-of-the-art accuracy and F1 scores.Results and discussionThese findings highlight the model's capacity to generalize across diverse datasets and capture fine-grained pose details, showcasing its potential in advancing complex pose recognition tasks. The proposed framework offers a robust solution for precise action recognition and paves the way for future developments in multi-modal pose analysis.